Click Construction of Spiro‐ and Bridged‐Quatrefoil Polymer Topologies with Kyklo‐Telechelics Having an Azide Group. Issue 4 (6th September 2013) - Ko, Yee Song; Yamamoto, Takuya; Tezuka, Yasuyuki; Lutz, J.‐F.; Sumerlin, B.; Matyjaszewski, K.
<x xml:space="preserve">Abstract</x> Unprecedented tetracyclic polymer topologies with spiro‐ and a bridged‐type quatrefoil forms are effectively constructed through an alkyne‐azide, click‐linking reaction by employing a kyklo‐telechelic poly(tetrahydrofuran), poly(THF), precursor having an azide group, obtained through an electrostatic self‐assembly and covalent fixation (ESA‐CF) process, and complementary tetrafunctional alkyne reagents of either a pentaerythritol derivative or a four‐armed star telechelic polymer precursor. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>